'No zone' approach to the management of stable penetrating neck injuries: a systematic review. Issue 6 (22nd January 2021) - Chandrananth, Meera L.; Zhang, Andrew; Voutier, Catherine R.; Skandarajah, Anita; Thomson, Benjamin N. J.; Shakerian, Rezvaneh; Read, David J.
Abstract: Background: Aim: to review outcomes of the 'no zone' approach to penetrating neck injuries (PNIs) with the advent of high‐fidelity computed tomography‐angiography (CT‐A) in order to determine the most appropriate management for stable PNIs. Design: Systematic review. Population: Retrospective and prospective cohort studies of patients who sustained penetrating neck trauma, as defined by an injury which penetrates the platysma, and whose initial management involved CT‐A evaluation. Methods: An extensive literature search was performed in July 2019 using the following databases: Pubmed Central, EMBASE, Medline and Cochrane CENTRAL. Only studies published in English from the last 15 years were included. Results: Nine cohort studies met inclusion criteria. There has been an increase in CT‐A focussed evaluation of PNIs in recent years. CT‐A is a highly sensitive and specific imaging choice and reduces negative neck exploration rates. A new management algorithm for stable patients involving initial radiological assessment using CT‐A, and subsequent selective surgical exploration, is safe and effective. Conclusion: The results of this review provide level 2A evidence that the 'no zone' approach to PNIs, complemented by CT‐A and thorough clinical assessment, is a safe management strategy which reduces negative neck exploration rates. Abstract : Penetrating neck injuries have traditionally been managed via a zone‐based approach, with mandatory exploration for all zone II injuries, which can lead to high negative neck exploration rates. We performed a systematic review examining the 'no zone' approach to penetrating neck injuries, with the use of high fidelity computed tomography angiography, to determine whether negative neck exploration rates can be reduced with this algorithm.